Computational chemical analysis of Ru(II)‐Pheox–catalyzed highly enantioselective intramolecular cyclopropanation reactions. Issue 1 (4th December 2018) - Nakagawa, Yoko; Nakayama, Naofumi; Goto, Hitoshi; Fujisawa, Ikuhide; Chanthamath, Soda; Shibatomi, Kazutaka; Iwasa, Seiji
Abstract: Computational chemical analysis of Ru(II)‐Pheox–catalyzed highly enantioselective intramolecular cyclopropanation reactions was performed using density functional theory (DFT). In this study, cyclopropane ring–fused γ‐lactones, which are 5.8 kcal/mol more stable than the corresponding minor enantiomer, are obtained as the major product. The results of the calculations suggest that the enantioselectivity of the Ru(II)‐Pheox–catalyzed intramolecular cyclopropanation reaction is affected by the energy differences between the starting structures5l and5i . The reaction pathway was found to be a stepwise mechanism that proceeds through the formation of a metallacyclobutane intermediate. This is the first example of a computational chemical analysis of enantioselective control in an intramolecular carbene‐transfer reaction using C 1 ‐symmetric catalysts. Abstract :